Desain Kurikulum PAUD untuk Guru Non-Kependidikan di Wilayah 3T : Kajian Literatur Berbasis Design Thinking - Setlight, Kharisma Caisar Mitania Syaumi; Haryono, Haryono (Jurnal Ilmiah Global Education, 2026)
Disparities in the quality of Early Childhood Education (ECE) services in underdeveloped, frontier, and outermost (3T) regions are often understood primarily as issues of limited facilities and infrastructure. However, a review of various studies indicates that a more fundamental problem lies in curriculum designs that are not fully grounded in the social, cultural, and professional realities of educators in these regions. Much of the existing ECE curriculum literature assumes the availability of professionally trained teachers with formal pedagogical backgrounds, rendering it less relevant to community-based ECE programs managed by non-education-trained teachers. This article presents a critical literature review of studies addressing contextual ECE curriculum design in 3T regions through a Design Thinking approach. The review is conducted using thematic analysis of national and international journal articles, academic books, and relevant conference proceedings. The synthesis of the literature reveals that Design Thinking offers a human-centered framework that enables curricula to be developed in an empathetic, participatory, and locally adaptive manner. Nevertheless, discussions on the integration of this approach into ECE curriculum design in 3T regions remain relatively limited. This article emphasizes the importance of developing a theoretical framework for ECE curricula grounded in field realities that is not only contextual but also positions non-education-trained teachers as key actors in the curriculum design process.